2023
DOI: 10.3390/nu15020339
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Serum 25-Hydroxyvitamin D Levels during Pregnancy and Postpartum—Are the Current Recommendations for Supplementation Sufficient?

Abstract: (1) Background: Pregnant women are at risk of vitamin D deficiency. Data on pregnancy outcomes in women with vitamin D deficiency during pregnancy are controversial, and prospective longitudinal data on vitamin D deficiency with consistent definitions in pregnant women are scarce. (2) Methods: The aim of this prospective longitudinal cohort study was to investigate 25-hydroxyvitamin D levels over the course of pregnancy and postpartum in singleton and twin pregnancies with regard to dietary and supplemental vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…VitD plays an important role in maintaining the bone health and overall health of pregnant women. Studies have shown that VitD deficiency during pregnancy may increase the risk of adverse pregnancy outcomes such as pre-eclampsia, gestational diabetes, low birth weight, and preterm birth (17)(18)(19)(20)(21)(22)(23). The study conducted by Lu et al revealed that vitamin D deficiency significantly increased the risk of gestational diabetes mellitus by 45% (21).…”
Section: Discussionmentioning
confidence: 99%
“…VitD plays an important role in maintaining the bone health and overall health of pregnant women. Studies have shown that VitD deficiency during pregnancy may increase the risk of adverse pregnancy outcomes such as pre-eclampsia, gestational diabetes, low birth weight, and preterm birth (17)(18)(19)(20)(21)(22)(23). The study conducted by Lu et al revealed that vitamin D deficiency significantly increased the risk of gestational diabetes mellitus by 45% (21).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have attempted to establish a link between low levels of 25-hydroxyvitamin D (the barometer of vitamin D status) and the occurrence of obstetric complications, but there is no consensus on this matter. Generally, pregnant women tend to develop vitamin D deficiency, reflected in both maternal and fetal serum levels of 25-hydroxyvitamin D, which should range from 30 to 100 ng/mL [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implementing vitamin D assessment and supplementation into routine obstetric practice may be a future trend [ 8 ]. Postpartum women are considered a high-risk population for vitamin D deficiency [ 9 ]. Some observational studies suggest a link between vitamin D levels and PPD [ 10 , 11 ], while other research has demonstrated no correlation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%